The Role Of Leadership In Improving The Engagement And Productiv-ity Of Human Resources In Educational Institutions - Joulanda A.M Rawis; Henny N. Tambingon; Jeffry S.J Lengkong (Eduvest - Journal of Universal Studies, 2024)
Human resources are an important aspect for the sustainability of an organization, including educational institutions. The existence of human resources helps educational institutions to achieve their goals. The success of educational institutions is closely related to the role of leadership in managing their human resources. The purpose of this study is to analyze the role of leadership in improving the engagement and productivity of human resources in educational institutions. The research method used is a qualitative method with data collection techniques using literature review, namely with the support of various literature studies. After the data is obtained, the data is analyzed with three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the role of leadership in increasing the involvement and productivity of human resources in educational institutions is vital, because effective leaders are able to create a work environment that supports and motivates educators and staff. By providing clear direction, constructive feedback and facilitation of skill development, strong leadership can improve overall team commitment and performance, making leadership a decisive factor in achieving greater educational goals.